2006
DOI: 10.1007/s10495-006-7689-z
|View full text |Cite
|
Sign up to set email alerts
|

The extrinsic and intrinsic apoptotic pathways are differentially affected by temperature upstream of mitochondrial damage

Abstract: It is well known that mild hypothermia prevents neuronal cell death following cerebral ischemia, although it can also cause apoptosis in other cell types. Thus, incubation at room temperature (RT) has been shown to induce apoptosis in hematopoietic cells, including Jurkat T leukemia cells. To further understand the apoptotic events that can be activated at RT, we compared the induction of apoptosis by several apoptotic insults in Jurkat cells stimulated at 37 degrees C or RT. Retinoid-related molecules, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 57 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Experimental models have shown that TH strongly inhibits the caspases pathway preventing apoptosis. The effect of hypothermia in theses pathways is such that makes it probably the therapeutic measure with the most benefit preventing neuronal apoptosis (Zhao et al, 2004; López-Hernández et al, 2006; Schmitt et al, 2007). …”
Section: Mechanisms Of Action Of Therapeutic Hypothermiamentioning
confidence: 99%
“…Experimental models have shown that TH strongly inhibits the caspases pathway preventing apoptosis. The effect of hypothermia in theses pathways is such that makes it probably the therapeutic measure with the most benefit preventing neuronal apoptosis (Zhao et al, 2004; López-Hernández et al, 2006; Schmitt et al, 2007). …”
Section: Mechanisms Of Action Of Therapeutic Hypothermiamentioning
confidence: 99%
“…The whole process of apoptotic execution is active at room temperature (RT; 19-251C), including membrane blebbing, except apoptotic body release. 27 Because caspases are normally active at RT, 27 there is a caspase-independent, temperaturedependent step in the process of apoptotic body release, which remains to be determined.…”
Section: The Apoptotic Network As An Integral Mechanism Of Controlmentioning
confidence: 99%
“…4C). Fas is a death domain-containing member of the tumor necrosis factor receptor superfamily that plays a central role in the physiological regulation of apoptosis (22). The Fas-mediated apoptosis pathway involves the activation of procaspases.…”
Section: Discussionmentioning
confidence: 99%